Diagnostic and prognostic value of troponin I in acute pulmonary embolism - Mohamed Moustafa Mohamed; Mahmoud Ali Elbadry; Mervat Mohamed Khalaf; Mohamed Ali Shehata (Cairo : Mohamed Moustafa Mohamed, 2010)
To determine the value of cardiac troponin I (cTnI ) in identifying the right ventricular dysfunction and severity of pulmonary embolism and its correlation to the inhospital outcome . Randomized prospective study . Department of critical care medicine Cairo University . A total of 30 critically - ill patients with acute pulmonary embolism
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical care Medicine
Issued also as CD
Keywords: Acute pulmonary embolism; RV dilatation; Troponin I